A New Class of Task-Specific Imidazolium Salts and Ionic Liquids and Their Corresponding Transition-Metal Complexes for Immobilization on Electrochemically Active Surfaces - Seidl, Vera; Romero Cordero, Angel Heriberto; Heinemann, Frank Wilhelm; Scheurer, Andreas; Vogel, Carola; Unruh, Tobias; Wasserscheid, Peter; Meyer, Karsten (Chemistry - A European Journal, 2022)
Adding to the versatile class of ionic liquids, we report the detailed structure and property analysis of a new class of asymmetrically substituted imidazolium salts, offering interesting thermal characteristics, such as liquid crystalline behavior, polymorphism or glass transitions. A scalable general synthetic procedure for N-polyaryl-N’-alkyl-functionalized imidazolium salts with para-substituted linker (L) moieties at the aryl chain, namely [LPhmImHR]+ (L=Br, CN, SMe, CO2Et, OH; m=2, 3; R=C12, PEGn; n=2, 3, 4), was developed. These imidazolium salts were studied by single-crystal X-ray diffraction (SC-XRD), NMR spectroscopy and thermochemical methods (DSC, TGA). Furthermore, these imidazolium salts were used as N-heterocyclic carbene (NHC) ligand precursors for mononuclear, first-row transition metal complexes (MnII, FeII, CoII, NiII, ZnII, CuI, AgI, AuI) and for the dinuclear Ti-supported Fe-NHC complex [(OPy)2Ti(OPh2ImC12)2(FeI2)] (OPy=pyridin-2-ylmethanolate). The complexes were studied concerning their structural and magnetic behavior via multi-nuclear NMR spectroscopy, SC-XRD analyses, variable temperature and field-dependent (VT-VF) SQUID magnetization methods, X-band EPR spectroscopy and, where appropriate, zero-field 57Fe Mössbauer spectroscopy.
CRIS-Team Scopus Importer:2022-03-25
Keywords: carbene ligands; electronic structure; ionic liquids; solid-state structure; thermal properties

An iron nitride complex - Vogel, Carola; Heinemann, Frank Wilhelm; Sutter, Jörg; Anthon, Christian; Meyer, Karsten (Angewandte Chemie International Edition, 2008)

Atomic diffusion in liquid gallium and gallium-nickel alloys probed by quasielastic neutron scattering and molecular dynamic simulations - Shahzad, Anjum; Yang, Fan; Steffen, Julien; Neiß, Christian; Panchenko, Artem; Götz, Klaus; Vogel, Carola; Weißer, Matthias; Embs, Jan Peter; Petry, Winfried; Lohstroh, Wiebke; Görling, Andreas; et al. (Journal of Physics: Condensed Matter, 2024)
The atomic mobility in liquid pure gallium and a gallium-nickel alloy with 2 at% of nickel is studied experimentally by incoherent quasielastic neutron scattering. The integral diffusion coefficients for all-atom diffusion are derived from the experimental data at different temperatures. DFT-based ab-initio molecular dynamics (MD) is used to find numerically the diffusion coefficient of liquid gallium at different temperatures, and numerical theory results well agree with the experimental findings at temperatures below 500 K. Machine learning force fields derived from ab-initio molecular dynamics (AIMD) overestimate within a small 6% error the diffusion coefficient of pure gallium within the genuine AIMD. However, they better agree with experiment for pure gallium and enable the numerical finding of the diffusion coefficient of nickel in the considered melted alloy along with the diffusion coefficient of gallium and integral diffusion coefficient, that agrees with the corresponding experimental values within the error bars. The temperature dependence of the gallium diffusion coefficient D Ga ( T ) follows the Arrhenius law experimentally for all studied temperatures and below 500 K also in the numerical simulations. However, D Ga ( T ) can be well described alternatively by an Einstein-Stokes dependence with the metallic liquid viscosity following the Arrhenius law, especially for the MD simulation results at all studied temperatures. Moreover, a novel variant of the excess entropy scaling theory rationalized our findings for gallium diffusion. Obtained values of the Arrhenius activation energies are profoundly different in the competing theoretical descriptions, which is explained by different temperature-dependent prefactors in the corresponding theories. The diffusion coefficient of gallium is significantly reduced (at the same temperature) in a melted alloy with natural nickel, even at a tiny 2 at% concentration of nickel, as compared with its pure gallium value. This highly surprising behavior contradicts the existing excess entropy scaling theories and opens a venue for further research.
CRIS-Team Scopus Importer:2024-02-16
Keywords: ab-initio molecular dynamics; DFT-based machine learning force fields; gallium-nickel alloy; liquid gallium; quasielastic neutron scattering; self-diffusion

Author Correction: Isolated Rh atoms in dehydrogenation catalysis (Scientific Reports, (2023), 13, 1, (4458), 10.1038/s41598-023-31157-y) - Wittkämper, Haiko; Hock, Rainer; Weißer, Matthias; Dallmann, Johannes; Vogel, Carola; Raman, Narayanan; Taccardi, Nicola; Haumann, Marco; Wasserscheid, Peter; Hsieh, Tzung En; Maisel, Sven; Moritz, Michael; et al. (Scientific Reports, 2023)
Correction to: Scientific Reports, published online 17 March 2023 The original version of this Article contained an error in the spelling of the author Nicola Taccardi, which was incorrectly given as Nicola Tacardi. The original Article has been corrected.
CRIS-Team Scopus Importer:2023-06-30

Effects of isotope and chemical incoherence on self-diffusion of atoms in liquid alloys of gallium with isotopes of nickel: Experiments based on quasielastic neutron scattering versus molecular dynamics simulations - Goychuk, Igor; Panchenko, Artem; Shahzad, Anjum; Fauser, Steffen; Neiß, Christian; Götz, Klaus; Vogel, Carola; Weißer, Matthias; Hakim, Bishoy; Embs, Jan Peter; Englhard, Jonas; Bachmann, Julien; et al. (Physical Review B, 2025)
Quasielastic neutron scattering (QENS) is a powerful experimental technique to investigate the diffusion of atoms in liquids. It relies on the fact that at low 𝑄 values essentially only incoherent scattering is observed from the diffusing atoms. In the case of alloys composed of two chemical elements, it is commonly believed that at low 𝑄 QENS mainly probes the self-diffusion of the element with a nonzero incoherent scattering cross-section, while the element with a zero incoherent scattering cross-section does not contribute. However, the findings of this study challenge this belief. The study examines alloys of natural gallium (which has a nonzero incoherent scattering cross-section) and isotopes 58 Ni and 60 Ni (both of which have a zero incoherent scattering cross-section). A crucial factor to consider here is chemical incoherence, which typically leads to the renormalization of the incoherent cross-sections of different chemical elements within a mixture. Unfortunately, this renormalization is often disregarded in an ad hoc manner. Significantly, the alloy containing 58 Ni shows a notable renormalization, scattering incoherently to a similar degree as natural nickel in a comparable alloy with equivalent concentrations of chemical elements. Similarly perplexing, natural nickel scatters with great intensity despite being predominantly composed of 58 Ni and 60 Ni (around 94% of the total). This behavior can be attributed to the accepted phenomenon of isotope incoherence. We calculate the integral diffusion coefficients of Ga and Ni atoms in various liquid alloys from QENS experiments. These values are then compared to the results obtained from corresponding molecular dynamics simulations conducted at various temperatures, taking into account chemical incoherence. The comparison shows good agreement within the range of errors for the Ga1−𝑥⁢ 58Ni𝑥 alloy at two concentrations (𝑥=0.02 and 𝑥=0.1). The agreement also partially holds for the Ga1−𝑥⁢Ni𝑥 alloy with natural nickel and for the Ga1−𝑥⁢ 60Ni𝑥 alloy, despite certain difficulties discusse
CRIS-Team Scopus Importer:2025-02-17
Keywords: Diffusion; Alloys; Liquid metals; Ab initio molecular dynamics; Molecular dynamics; Neutron scattering

Isolated Rh atoms in dehydrogenation catalysis - Wittkämper, Haiko; Hock, Rainer; Weißer, Matthias; Dallmann, Johannes; Vogel, Carola; Raman, Narayanan; Tacardi, Nicola; Haumann, Marco; Wasserscheid, Peter; Hsieh, Tzung En; Maisel, Sven; Moritz, Michael; et al. (Scientific Reports, 2023)
Isolated active sites have great potential to be highly efficient and stable in heterogeneous catalysis, while enabling low costs due to the low transition metal content. Herein, we present results on the synthesis, first catalytic trials, and characterization of the Ga9Rh2 phase and the hitherto not-studied Ga3Rh phase. We used XRD and TEM for structural characterization, and with XPS, EDX we accessed the chemical composition and electronic structure of the intermetallic compounds. In combination with catalytic tests of these phases in the challenging propane dehydrogenation and by DFT calculations, we obtain a comprehensive picture of these novel catalyst materials. Their specific crystallographic structure leads to isolated Rhodium sites, which is proposed to be the decisive factor for the catalytic properties of the systems.
CRIS-Team Scopus Importer:2023-03-31

Mesoscopic Structure of Lipid Nanoparticle Formulations for mRNA Drug Delivery: Comirnaty and Drug-Free Dispersions - Unruh, Tobias; Götz, Klaus; Vogel, Carola; Fröhlich, Erik; Scheurer, Andreas; Porcar, Lionel; Steiniger, Frank (ACS nano, 2024)
Lipid nanoparticles (LNPs) produced by antisolvent precipitation (ASP) are used in formulations for mRNA drug delivery. The mesoscopic structure of such complex multicomponent and polydisperse nanoparticulate systems is most relevant for their drug delivery properties, medical efficiency, shelf life, and possible side effects. However, the knowledge on the structural details of such formulations is very limited. Essentially no such information is publicly available for pharmaceutical dispersions approved by numerous medicine agencies for the use in humans and loaded with mRNA encoding a mimic of the spike protein of the severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) as, e.g., the Comirnaty formulation (BioNTech/Pfizer). Here, we present a simple preparation method to mimic the Comirnaty drug-free LNPs including a comparison of their structural properties with those of Comirnaty. Strong evidence for the liquid state of the LNPs in both systems is found in contrast to the designation of the LNPs as solid lipid nanoparticles by BioNTech. An exceptionally detailed and reliable structural model for the LNPs i.a. revealing their unexpected narrow size distribution will be presented based on a combined small-angle X-ray scattering and photon correlation spectroscopy (SAXS/PCS) evaluation method. The results from this experimental approach are supported by light microscopy, 1H NMR spectroscopy, Raman spectroscopy, cryogenic electron microscopy (cryoTEM), and simultaneous SAXS/SANS studies. The presented results do not provide direct insights on particle formation or dispersion stability but should contribute significantly to better understanding the LNP drug delivery process, enhancing their medical benefit, and reducing side effects.
CRIS-Team Scopus Importer:2024-04-12
Keywords: BNT162b2 Comirnaty; dynamic light scattering (DLS; lipid nanoparticles (LNPs); mRNA drug delivery; PCS); proton nuclear magnetic resonance spectroscopy (; severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2); small-angle X-ray scattering (SAXS)

Redox control of a polymerization catalyst by changing the oxidation state of the metal center - Broderick, Erin M.; Guo, Neng; Wu, Tianpin; Vogel, Carola; Xu, Cuiling; Sutter, Jörg; Miller, Jeffrey T.; Meyer, Karsten; Cantat, Thibault; Diaconescu, Paula L. (Chemical Communications, 2011)

Redox control of a ring-opening polymerization catalyst - Broderick, Erin M.; Guo, Neng; Vogel, Carola; Xu, Cuiling; Sutter, Jörg; Miller, Jeffrey T.; Meyer, Karsten; Mehrkhodavandi, Parisa; Diaconescu, Paula L. (Journal of the American Chemical Society, 2011)

Solid-state structures of double-long-chain imidazolium ionic liquids: Influence of anion shape on cation geometry and crystal packing - Wang, Xinjiao; Vogel, Carola; Heinemann, Frank Wilhelm; Wasserscheid, Peter; Meyer, Karsten (Crystal Growth & Design, 2011)
The syntheses and solid-state structures of a series of imidazolium (IM) salt-based, double C alkyl chain functionalized ionic liquids, namely, [CCIM] [A], where the anion A is I , I, I, N(CN) , C(CN), B(CN), or SbF, are reported. All compounds were fully characterized by CHN elemental analysis, H and C NMR spectroscopy, and X-ray diffraction studies on single crystals. The molecular structure of the IM [CCIM] cation, as found in the individual crystal packing arrangements, is discussed in relation to the different anions used for crystallization. Depending on the geometry of the counteranions used (linear, bent, planar, and spherical), different molecular structures of the IM cations (rod-, V-, and U-shaped) resulted. The crystal packing in the solid-state structure is examined on the basis of a Hirshfeld surface analysis and is discussed in terms of polar and nonpolar regions. © 2011 American Chemical Society.

Spin crossover in a four-coordinate iron(II) complex - Scepaniak, Jeremiah J.; Harris, T. David; Vogel, Carola; Sutter, Jörg; Meyer, Karsten; Smith, Jeremy M. (Journal of the American Chemical Society, 2011)

Synthesis and characterization of cerium and yttrium alkoxide complexes supported by ferrocene-based chelating ligands - Broderick, Erin M.; Thuy-Boun, Peter S.; Guo, Neng; Vogel, Carola; Sutter, Jörg; Miller, Jeffrey T.; Meyer, Karsten; Diaconescu, Paula L. (Inorganic Chemistry, 2011)
Two series of Schiff base metal complexes were investigated, where each series was supported by an ancillary ligand incorporating a ferrocene backbone and different N=X functionalities. One ligand is based on an imine, while the other is based on an iminophosphorane group. Cerium(IV), cerium(III), and yttrium(III) alkoxide complexes supported by the two ligands were synthesized. All metal complexes were characterized by cyclic voltammetry. Additionally, NMR, Mössbauer, X-ray absorption near-edge structure (XANES), and absorption spectroscopies were used. The experimental data indicate that iron remains in the +2 oxidation state and that cerium(IV) does not engage in a redox behavior with the ancillary ligand. © 2011 American Chemical Society.

Synthesis, structure, and reactivity of an iron(V) nitride - Scepaniak, Jeremiah J.; Vogel, Carola; Khusniyarov, Marat; Heinemann, Frank Wilhelm; Meyer, Karsten; Smith, Jeremy M. (Science, 2011)
Despite being implicated as important intermediates, iron(V) compounds have proven very challenging to isolate and characterize. Here, we report the preparation of the iron(V) nitrido complex, [PhB( BuIm) Fe ≡N]BAr (PhB( BuIm) = phenyltris(3-tert-butylimidazol-2-ylidene)borato, BAr = B(3,5-(CF ) C H ) ), by one electron oxidation of the iron(IV) nitrido precursor. Single-crystal x-ray diffraction of the iron(V) complex reveals a four-coordinate metal ion with a terminal nitrido ligand. Mößbauer and electron paramagnetic resonance spectroscopic characterization, supported by electronic structure calculations, provide evidence for a d iron(V) metal center in a low spin (S = 1/2) electron configuration. Low-temperature reaction of the iron(V) nitrido complex with water under reducing conditions leads to high yields of ammonia with concomitant formation of an iron(II) species.

Unexpected reactivity resulting from modifications of the ligand periphery: Synthesis, structure, and spectroscopic properties of iron complexes of new tripodal N-heterocyclic carbene (NHC) ligands - Vogel, Carola; Heinemann, Frank Wilhelm; Khusniyarov, Marat; Meyer, Karsten (Inorganica Chimica Acta, 2010)
The chelating ligand tris-[2-(3-aryl-imidazol-2-ylidene)ethyl]amine (TIMEN, R = aryl = 2,6-xylyl (xyl), mesityl (mes)) has provided access to reactive transition metal complexes. Here, two new tripodal N-heterocyclic carbene ligands of the TIMEN system (R = aryl = tolyl (tol), 3,5-xylyl (3,5xyl)), featuring sterically less demanding aryl substituents were synthesized. With these ligands, Fe(II) precursor complexes could be obtained, namely [(TIMEN)Fe](BF) (3) and [(TIMEN)Fe(CHCN)](PF) (7), which showed unexpected reactivity upon reduction. Treatment of the compounds with sodium amalgam yield the tris- and bis-metallated products, [(TIMEN)Fe] (4) and [(TIMEN)Fe] (8), respectively. While the Fe(III) complex 4 is relatively inert towards oxygen, the Fe(II) complex 8 is prone to oxidation. This oxidation of 8 can readily be observed in chlorinated solvents, producing the Fe(III) complex [(TIMEN )Fe](PF) (9). All new ligand imidazolium precursors and metal complexes were characterized by single crystal X-ray structure determination. © 2010 Elsevier B.V. All rights reserved.